2008
DOI: 10.1159/000177015
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Balloon Dilation of Anastomotic Strictures Occurring after Laparoscopic Gastric Bypass for Morbid Obesity

Abstract: Background: Gastrojejunal anastomotic stenosis of laparoscopic Roux-en-Y gastric bypass (LRYGB) for morbid obesity occurs in 3–25% of cases. The aim of this report was to evaluate the utility of endoscopic balloon dilation for the therapy of anastomotic strictures after LRYGB. Patients and Methods: 111 consecutive patients were treated with endoscopic dilation under sedation with propofol. Dilations were performed with through-the-scope over-the-wire balloons, with sizes ranging from 6 to 18 mm. The outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
3
11
0
2
Order By: Relevance
“…A total of 1,298 dilations were performed in the 760 patients included in the review, which was an average of 1.7 dilations per patient. This was consistent with the data reported by Caro et al 6 , who reported 1.8 dilations per patients. The studies indicated that this complication of surgery could be resolved with a small number of dilation procedures, with endoscopy being the best treatment choice.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A total of 1,298 dilations were performed in the 760 patients included in the review, which was an average of 1.7 dilations per patient. This was consistent with the data reported by Caro et al 6 , who reported 1.8 dilations per patients. The studies indicated that this complication of surgery could be resolved with a small number of dilation procedures, with endoscopy being the best treatment choice.…”
Section: Discussionsupporting
confidence: 93%
“…One (8%) left the balloon inflated until the waist disappeared, followed by another dilation lasting 30-60 s 19 . Seven studies reported complications 6,11,17,20,23,26,29 (T able 4). Perforation was the most common complication, reported in 14 patients (1.82%) and requiring immediate operation in two patients 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caro et al reviewed 111 patients that had undergone endoscopic balloon dilatation following RYGB 50 and reported two perforations and one hematoma of the esophagus following a total of 200 endoscopic dilatations. An average of 2.2 endoscopic dilatations per patient were needed to treat gastrojejunal strictures post-RYGB.…”
Section: The Role Of Endoscopy Postoperative To Detect and Treat Anasmentioning
confidence: 99%
“…The stenosis of the stoma (stenosis of the gastro-jejunal anastomosis) occurs in approximately 3-12% after gastric bypass, and must be suspected when the patient experiences dysphagia, nausea and vomiting (2)(3)(4)(5)(6)(7)(8)(9). Endoscopic dilation of the stenosis by means of a balloon or bougie is considered the treatment of choice, even if in most studies it is not quite clear whether it should be done with or without a radioscopic guidance (4)(5)(6)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) In this study, we informed of our experience in the management of the stenosis of the stoma in patients with laparoscopic gastric bypass by means of endoscopic dilation with a hydrostatic balloon, without fluoroscopic guidance.…”
Section: Introductionmentioning
confidence: 99%